The Effectiveness of closed kinetic chain exercises in individuals with knee osteoarthritis: A systematic review and meta-analysis - Ammar Fadil; Qassim Ibrahim Muaidi; Mohamed Salaheldien Alayat; Nahla Ahmad AlMatrafi; Moayad Saleh Subahi; Mansour Abdullah Alshehri (PLoS ONE, 2025)
Introduction The aims of this review was to investigate the effectiveness of closed kinetic chain exercise (CKCE) on pain, function, and proprioception in individuals with knee osteoarthritis (OA). Methods Nine databases were searched up to December 2023. Randomized controlled trials (RCTs) examining the effects of CKCE in individuals with knee OA were included. The methodological quality was assessed using the PEDro scale, and the level of evidence was evaluated with the GRADE system. A random-effects meta-analysis was conducted to assess differences between treatment groups for the primary outcomes (pain and function). Effect sizes were calculated using standardized mean differences (SMDs) with 95% confidence intervals (CIs). Results A total of 24 studies were included in the descriptive analysis, and 18 studies were included in the quantitative analysis (meta-analysis). The meta-analysis results indicated that CKCE treatment led to greater improvements in pain (SMD = −0.76; 95% CI: −1.51, −0.01) and function (SMD = −1.25; 95% CI: −1.88, −0.62) compared to no treatment. A subgroup meta-analysis showed that the combined treatment of CKCE and conventional physical therapy (CPT) resulted in greater improvements in pain (SMD = −1.18; 95% CI: −1.70, −0.67) and function (SMD = −1.27; 95% CI: −1.79, −0.75) compared to CPT alone. The risk of bias assessment revealed that two studies were of low quality, nine were of fair quality, and the remaining 13 were of high quality. The GRADE system indicated a low quality of evidence for the effects of CKCE on both pain and function. Conclusion While CKCE shows promise in reducing pain and improving function in individuals with knee OA, the quality of evidence is considered low according to the GRADE system. Further high-quality RCTs with larger sample sizes are needed to confirm the effectiveness of CKCE in managing knee OA.